Reading the Transformation of The Alun-Alun in Bogor City as a Physical and Social Space - Megisterina; Devvy Alvionita Fitriana; Kohdrata, Naniek (Institute for Research and Community Services Udayana University, 2026)
The dichotomy of study in STEM (science technology engineering and mathematics) and the humanities has been a popular issue in academic research. This paper tries to see whether that the dichotomy is significant or not. Utilizing a public open space as one of the common subjects of study in landscape architecture. The public open space is analyzed within a positivistic domain and in the cultural studies paradigm. The purpose is to exercise an approach of analyzing a same set of data and present a continuous discussion on the subject of interest, which is alun-alun (town square). Data from two town squares in Bogor City, which are Alun-alun Empang and Alun-alun Kota Bogor, were collected according to common practice in landscape architecture field of study. The discussion uses descriptive analysis and critical social analysis techniques. The result shows that descriptive analysis works well for biophysical aspect while the critical social analysis makes the social aspect give a deeper understanding on intangible area.